Simple Synthesis of CeO2 Nanoparticle Composites In Situ Grown on Carbon Nanotubes for Phenol Detection - Hu, Chao; Huang, Haiping; Yan, Yu; Hu, Yongmei; Liu, Sui-Jun; Wen, He-Rui (Frontiers in Chemistry, 2022)
via simple hydrothermal method, CeO2 was in-situ grown onto the CNTs to form CeO2/CNTs nanocomposites were synthesized with cerium nitrate as Ce resource. The morphology and structure were characterized by transmission electron microscopy and X-ray diffraction. The characterizations reveal that CeO2 nanoparticles are uniformly dispersed onto the surface of the pre-acidified CNTs. The electrochemical property of the synthesized nanocomposite was investigated in 0.1 M KCl electrolyte containing 2 mM [Fe(CN)6]3-/4-. The nanocomposites were employed to fabricate electrochemical sensor for phenol detection. The linear range for phenol detection measured by the differential pulse voltammetry method is 1-500 μM. The sensor also exhibits good selectivity, reproducibility and stability. When applied for the river and tap water analysis, it shows good recovery rate.